2023
DOI: 10.1021/acsami.2c18694
|View full text |Cite
|
Sign up to set email alerts
|

Robust Carbon Nitride Homojunction Photoelectrode for Solar-Driven Water Splitting

Abstract: Achieving intimate particle-to-particle and particle-to-substrate contacts is the first priority for fabricating high-quality photoelectrodes to ensure sufficient visible light absorption and efficient charge separation/transport. To achieve this goal, a seeding strategy is designed to construct a robust carbon nitride (CN) homojunction photoelectrode, in which vaporized precursors are condensed into a compact seeding layer at low temperatures, inducing the further deposition of the top layer. This optimized p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…CN-based polymers have also recently attracted extensive attention for photo-electrochemical (PEC) water splitting and organic transformations; [118][119][120][121][122] however, the search for suitable techniques to deposit high-quality layers of crystalline CN materials in good contact with the electrode is an ongoing challenge. Very recently, progress in the different deposition techniques developed in the state of the art to create CN layers has been reported in review articles, to which we would like to refer the reader.…”
Section: Enhanced Charge Transfer In Photoelectric Devicesmentioning
confidence: 99%
“…CN-based polymers have also recently attracted extensive attention for photo-electrochemical (PEC) water splitting and organic transformations; [118][119][120][121][122] however, the search for suitable techniques to deposit high-quality layers of crystalline CN materials in good contact with the electrode is an ongoing challenge. Very recently, progress in the different deposition techniques developed in the state of the art to create CN layers has been reported in review articles, to which we would like to refer the reader.…”
Section: Enhanced Charge Transfer In Photoelectric Devicesmentioning
confidence: 99%
“…The onset potential is as low as 0.034 V. The OER faradaic efficiency is up to 83%. 39 β-FeOOH was deposited on an in situ synthesized homojunction CN photoanode, which achieved over 320 μA cm −2 at 1.23 V. 174 Another study reported that a Ni atom imbedded phenyl-modified CN electrode extended the light absorption, and accelerated the charge separation and transfer, and meanwhile Ni accelerated water oxidation kinetics, leading to better PEC performance. 35 Liu et al incorporated Co 2+ species into a microprinted CN pattern photoanode, in which Co sites act as OER active sites in the PEC water splitting application.…”
Section: Photoelectrochemical Water Splitting Of Cn Filmsmentioning
confidence: 99%
“…As we know, solar energy has long been applied in water splitting, where catalysts in the anode must be photoactive semiconductors with energy gaps smaller than the energy of photons [57][58][59]. Recently, a photoanode of WO 3 was utilised as the catalyst to decouple HER and OER in a photoelectrochemical cell.…”
Section: Photocatalysismentioning
confidence: 99%